Location of the Bacillus subtilis temperate bacteriophage phi 105 attP attachment site. - Ellis, D M (1986)
Chromosomal DNAs of lysogens of phi 105 and phi 105 DI:1t were digested with restriction enzymes EcoRI and HpaI and were probed with nick-translated mature phi 105 DNA. Altered bacteriophage-specific bands in the lysogens were detected, indicating that the phage integrates into the host chromosome at a single site, probably via a Campbell-type circular intermediate. The phage attachment site is centrally located in the phage genome and lies between the phage immunity region and the nonessential deletable region of phi 105.